Law and practice of evidence in Nigeria in Nigeria - Babalola, Afe (Ibadan, Nigeria Sibon Books Ltd., 2001)
Chief Afe Babalola S. A. N. is coming out again with another book in law. The book on Injunctions and Enforcement of Orders he published last year has been aptly described as 'a goldmine to all interested in the sustenance of the rule of law and attainment of substantive justice." This book on law of evidence has much to commend it both in concept and execution.
includes index
aau, 2/08/2022
Loan